Scientific and Methodical Basis of Normalization of Loads in Physical Education and Public Sports Health Care - A.M.Mukhammetov (Genius Publishing Group, 2022)
This article discusses the issues of normalization and proper conduct of physical education and public health training, as well as possible methodological recommendations.
Keywords: Training; loads; sports; skills